Pengembangan Media Pembelajaran Berbantuan Lectora Inspire pada Materi Reaksi Redoks - Adelila Sari, Sri; Haripah Rambe, Julianda; Hasibuan, Hanisah (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
Lack of a variety of learning media was one of the issues contributing to poor student learning results in chemistry. One of the subjects that students found challenging was redox material since it involves complicated and abstract concepts that call for a thorough knowledge in order to grasp them. The goal of this study was to create educational materials on redox reactions with the help of Lectora Inspire. Up to 30 people participated in this study at SMA Negeri 1 Batang Kuis in class X, IPA 5. Research and development (R&D) was the approach employed, and the ADDIE paradigm, which has five parts (analysis, design, development, implementation, and evaluation), was used. At the analysis stage, needs and idea analysis were completed. The collection of analytical data was carried out using interview sheet and questionnaire. Furthermore, the learning media helped by lectora inspire was conceived and developed. The developed media was validated by media expert validators who were also material expert validators as many as 3 Unimed chemistry lecturers by providing questionnaires based on criteria following the National Education Standards Agency (BNSP), namely the feasibility of content, language, presentation, and graphics. In addition, to measure student learning outcomes utilizing pre-test and post-test questions. The results of the research at the analysis stage achieved in the chemistry learning process in students still tend to find it difficult to understand concepts and calculations in chemistry learning and students consider chemistry a boring topic. In addition, the findings of the material expert assessment were achieved with an average percentage of 92% with a very feasible category, media expert evaluation with an average percentage of 90% with a very feasible category. While the learning results were acquired from the average of N-gain value, which was 0.7 with the medium category, where the averages of pre test and post test were determined to be 35.33 and 80.33, respectively. Therefore, those had met the minimal completeness condition ≥75. Thus, the learning media helped by lectora inspire on redox reaction content has met the BSNP standard criteria and was suitable for use as a learning media and students learning outcomes might be improved.